Anna Maria Maiolino from the perspective of process criticism: traces of creation: traces of creation - Gonçalves, Vinícius de Oliveira; Salles, Cecilia Almeida (Revista do Instituto de Estudos Brasileiros, 2020)
The article aims to discuss Anna Maria Maiolino's work from the perspective of her process of creation. It will present the academic context in which the research is inserted: a group of studies that proposes the critique of creative processes as a possible approach to art. A line of research that deals with the records, left by artists, along their artistic paths. We highlight the relevance of proposing a critical theory of process in the face of contemporary artistic experimentation and interrogation involving the exploration of archives and the different relations between work and process. This artist's work offers an interesting space for such reflections. From some general aspects of the process, special emphasis will be given to the following aspects: publication of process documents, procedural works, processes becoming works and intersemiotic texture.